Passage performance of long-distance upstream migrants at a large dam on the Paraná River and the compounding effects of entry and ascent - Wagner,Ricardo Luiz (2012)
This paper presents results of a fishway evaluation performed at the Engenheiro Sérgio Motta Hydroelectric Power Plant (known as Porto Primavera) - CESP, Paraná River, Brazil. The evaluation was designed to quantify entry and passage proportions of 4 long-distance migratory fish species: Brycon orbignyanus (piracanjuba), Piaractus mesopotamicus (pacu), Prochilodus lineatus (curimba), and Rhinelepis aspera (cascudo-preto). Proportions finding and entering the fishway differed between species, ranged from 7.4 % (Prochilodus lineatus) to 55.4% (Piaractus mesopotamicus). Also, proportion passing was different between species, ranged from 31% (R. aspera) to 100% (Prochilodus lineatus). Fish that were marked and released within the fishway had greater failure rates than those that entered volitionally. Total time to pass ranged from 1.48 hours (Prochilodus lineatus) to 178.9 hours (R. aspera). Failure rates were greatest in the lower end of the fishway. Although some individuals of all species passed successfully, significant challenges remain to restoring connectivity of the upper Paraná River.